2019
DOI: 10.1007/s10483-019-2542-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency and broadband vibration energy harvester driven by mechanical impact based on layer-separated piezoelectric beam

Abstract: Vibration energy harvesting is to transform the ambient mechanical energy to electricity. How to reduce the resonance frequency and improve the conversion efficiency is very important. In this paper, a layer-separated piezoelectric cantilever beam is proposed for the vibration energy harvester (VEH) for low-frequency and wide-bandwidth operation, which can transform the mechanical impact energy to electric energy. First, the electromechanical coupling equation is obtained by the Euler-Bernoulli beam theory. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
0
6
1
Order By: Relevance
“…Comparing with the previous research work (Cao et al, 2019c), it is found that the first and second resonant frequencies of the partial separated VEH are smaller than that of the complete separated VEH. The results show the advantages of lower frequency and broad bandwidth energy harvesting.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Comparing with the previous research work (Cao et al, 2019c), it is found that the first and second resonant frequencies of the partial separated VEH are smaller than that of the complete separated VEH. The results show the advantages of lower frequency and broad bandwidth energy harvesting.…”
Section: Discussioncontrasting
confidence: 59%
“…However, conventional vibro-impact VEHs need much more space to assemble the driving system, impactor or magnet, that is disadvantageous to expand the engineering applications especially for the integration with micro-electro-mechanical system. In order to overcome these issues, the authors (Cao et al, 2019c) proposed a layer-separated vibration energy harvester based on vibro-impact model, where there is no need any other impactor. The results show that it's realizable to scavenge the vibration energy.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the electromechanical coupling equation of the enhanced PFEH, the piezoelectric stack is regarded as a single degree-of-freedom system, see Figure 3(e). As aforementioned, the dynamic equation of the piezoelectric stack under the excitation force 𝐹 π‘œπ‘’π‘‘ can be expressed as π‘š 𝑆 π‘¦Μˆ+ 𝐢 𝑆 𝑦̇+ 𝐾 𝑆 𝑦 = 𝐹 π‘œπ‘’π‘‘ (11) in which 𝑦 is the longitudinal vibration displacement of the piezoelectric stack, 𝐢 𝑠 is a damping coefficient of the system, π‘š 𝑆 = π‘πœŒπ‘‘π‘† 3…”
Section: Electromechanical Coupling Equationsmentioning
confidence: 99%
“…Vibrationbased energy harvesting (VEH) techniques, which can transform ambient mechanical energy from external sources to electric energy, is an ideal solution to drive small-scale and wireless devices, like those used in wearable electronics and wireless sensors. In recent years, a plenty of research studies have devoted great efforts on different technologies of VEH, and various transduction mechanisms have been used, such as electrostatic [1][2][3], electromagnetic [4][5][6], piezoelectric [7][8][9][10][11] and ferroelectric approaches [12][13][14][15]. On the other hand, many structure forms have been proposed to improve and enhance the performance of vibration energy harvesters, including bi-stable [16][17][18], multi-stable [19][20][21][22] and multi-degree models [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical base structure is used to collect the vibration energy and transfer it to the piezoelectric elements. Different types of nonlinear structures, e.g., impact structures [23][24] , frequency up-conversion [25] , monostable structures [26] , and multi-stable structures [27][28][29] , have been developed to broaden the working bandwidth of piezoelectric energy harvesters (PEHs) [30] so as to improve the total harvested energy and environment serviceability [31][32][33] . Researchers have also concentrated on improving piezoelectric materials to enhance the dielectric property, storage capacity, stability, and piezoelectricity [34][35][36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%